Estimating cost implications of potentially avoidable hospitalizations among oncology care model patients with prostate cancer. (March 2020) - Smith, William H.; Parikh, Anish B.; Li, Lihua; Sanderson, Mark; Liu, Mark; Mazumdar, Madhu; Isola, Luis M.; Dharmarajan, Kavita V.
Highlights: Potentially avoidable hospitalizations (PAH) represent a cost savings opportunity. Unavoidable hospitalizations were more costly than PAHs. PAHs accounted for 5.8% of total oncology care model expenditures. Shifting PAHs to the ambulatory setting may result in significant cost savings. Abstract: Purpose/Objectives: We sought to estimate the expected cost savings generated if a set of potentially avoidable hospitalizations (PAHs) among oncology care model (OCM) patients with prostate cancer were shifted to an acute care model in the outpatient setting. Methods: We previously identified a set of 28 PAHs among OCM prostate cancer patients. Outpatient management costs for a characteristically similar cohort of cancer patients were obtained from our institution's ambulatory acute-care Oncology Care Unit (OCU). We excluded OCU visits resulting in hospitalization, involving non-cancer diagnoses, and those missing clinical/financial information. Exact-matching based on the strata of age, categorically-defined presenting complaint, and systemic disease was used to match PAHs to OCU acute care visits. PAH costs obtained from OCM data were compared to costs from matched OCU visits. Results: We identified 130 acute care OCU visits, of which 47 met inclusion criteria. Twenty-four PAHs (89%) matched to 26 of these OCU visits. PAHs accounted for 5.8% of OCM expenditures during our study period. The mean inpatient cost among matched PAHs was 15, 885 compared to 6227 for matched OCU visits. Boot strapping within each match stratum produced a mean estimated cost savings of 12, 151 (95% CI 10, 488 to 13, 814) per PAH. We estimate this per event savings to yield a 4.4% (95% CI 3.8% to 5.0%) an overall spending decrement for OCM prostate cancer episodes. Conclusions: PAHs contribute meaningfully to costs of care in oncology. Investment in specialized ambulatory acute care services for oncology patients could lead to substantial cost savings.